Mapping innovation and diffusion of hydrogen fuel cell technologies: Evidence from the UK's hydrogen fuel cell technological innovation system, 1954–2012. (15th November 2019) - Hacking, Nick; Pearson, Peter; Eames, Malcolm
Abstract: With the global sustainability transition in energy, hydrogen fuel cell (HFC) applications currently have important niche roles to play across several industrial sectors. Theorists examining this innovative activity have identified key socio-technical factors affecting the nature and pace of change. One functional approach to innovation, Technology-Specific Innovation Systems (TSISs), places national HFC Technological Innovation Systems (TISs) within a framework of a global HFC TSIS. This analytical approach suggests that HFC innovation can start anywhere in space. However, in a case study of HFC innovation and diffusion in the UK covering sixty years' activity, this theoretical assumption is challenged. Event history analysis and interviews using a neofunctionalist TSIS approach suggest that positive feedback was on the brink of occurring in the UK HFC TIS by 2012. When additional organisational and spatial indicators are added, the evidence on the ground does not support the aspatial assumptions that underlie TIS heuristic thinking. Rather, it suggested that type of investment funding and spatial location can influence HFC innovation. In this context, the implications for HFC policy in the UK are discussed. Highlights: New analysis of 60 years of hydrogen fuel cell (HFC) innovation in the UK. Technology-specific Innovation Systems approach shows positive innovation feedback. Evidence suggests the value of additional indicators to this approach. New funding source indicators help analyse innovation system resilience and policy. Spatial location indicators show that it matters where HFC innovation happens.